Social Media Treatment of Kurdistan Regional Channels in Coverage of Political Issues in the Kurdistan Region (A Non-Analytical Survey) - مەحەمەد, شێركۆ جبار (Sulaimani Journal for Humanities, 2019)
The aims of this research is to identify how the social media sites of the satellite channels deal with the coverage of political issues in the Kurdistan Region of Iraq and the objectives and motives of the communicators in the issues, controls and standards they adopt during the coverage and publication process. The survey methodology was used to use the content analysis method by means of the content analysis tool on a random non-random sample of the social media sites of the Kurdish satellite channels, which represented both the Rudaw and NRT channels over a period of time in January 2018. The analysis of content The political media on political media sites ranked first (26.3%), and the method of relying on sound and visual effects was the first among the methods of presenting political topics On those sites by 38.3%, and the level of nature of the publication of comments of members in those sites came comments (criticism performance of the government) ranked first by 40.5%.